mTOR-Mediated Regulation of Dendritic Cell Differentiation and Function - Sukhbaatar, Nyamdelger; Hengstschläger, Markus; Weichhart, Thomas (Trends in immunology, 2016)
Dendritic cells (DCs) are essential antigen-presenting cells that sample the extra- and intracellular milieu to process antigens for the instruction of T cell responses. The mammalian target of rapamycin (mTOR) network senses environmental cues and is important for numerous cellular processes. This review discusses how DCs use mTOR complexes (mTORC1 and 2) to adapt their cellular metabolism, transcriptional responses, and translation machinery to control DC development, antigen processing, cytokine production, and T cell stimulation. We present a spatiotemporal model suggesting that the mTOR network integrates pattern recognition and growth factor receptor activation with nutritional information from the cell and surrounding tissue to support T cell stimulation and tolerance. mTOR develops into a central player that regulates DC differentiation and immune functions. Precisely regulated mammalian target of rapamycin (mTOR) activity is important for dendritic cell (DC) development and function. mTOR complex 1 (mTORC1) senses the various nutritional environments that exist in tissues or lymph nodes and adjusts immune functions. DCs optimize antigen presentation by mTORC1-mediated control of autophagy, lysosome biogenesis, and MHC II expression. Control of protein synthesis by mTORC1 emerges as an important way to regulate inflammatory and immunomodulatory cytokine production in DCs. Inhibition of mTORC1 or mTORC2 in Toll-like receptor (TLR)-stimulated DCs enhances T cell stimulation and has been harnessed as a vaccine ‘adjuvant’. At steady state, inhibition of mTORC1 in non-activated DCs may enhance the generation of regulatory T cells.